2015
DOI: 10.1016/j.psychres.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Metamemory in schizophrenia: Retrospective confidence ratings interact with neurocognitive deficits

Abstract: Prior studies with schizophrenia patients described a reduced ability to discriminate between correct and false memories in terms of confidence compared to control groups. This metamemory bias has been associated with the emergence and maintenance of delusions. The relation to neuropsychological performance and other clinical dimensions is incompletely understood. In a cross-sectional study, metamemory functioning was explored in 32 schizophrenia patients and 25 healthy controls. Metamemory was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 72 publications
2
41
2
Order By: Relevance
“…Information can either be verbal (word recognition) or visual (picture recognition) in nature. However, the verbal paradigm has been implemented more often (Laws and Bhatt, 2005; Bhatt et al, 2010; Moritz et al, 2014b; Eifler et al, 2015; Eisenacher et al, 2015; Hodgetts et al, 2015). In this version, participants are usually asked to encode lists of words which are strongly associated with a not presented lure or “theme” word.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Information can either be verbal (word recognition) or visual (picture recognition) in nature. However, the verbal paradigm has been implemented more often (Laws and Bhatt, 2005; Bhatt et al, 2010; Moritz et al, 2014b; Eifler et al, 2015; Eisenacher et al, 2015; Hodgetts et al, 2015). In this version, participants are usually asked to encode lists of words which are strongly associated with a not presented lure or “theme” word.…”
Section: Methodsmentioning
confidence: 99%
“…Higher confidences in errors could be found persistently in patients with schizophrenia irrespective of the implemented task design. In contrast to healthy control groups these studies robustly suggested a biased metamemory performance (Moritz and Woodward, 2002; Moritz et al, 2003, 2004, 2005, 2006a; Kircher et al, 2007; Bhatt et al, 2010; Peters et al, 2012, 2013; Eifler et al, 2015), apart from one exception (Bacon et al, 2001). Moritz and Woodward (2002) were the first to compare the previously described source monitoring task between patients with schizophrenia and a healthy control group.…”
Section: Metamemory Functioning Over the Course Of Illnessmentioning
confidence: 97%
See 3 more Smart Citations